Evaluating Quality Indicators of Glioblastoma Care: Audit Results From an Indian Tertiary Care Cancer Center. (17th March 2022) - Basu Achari, Rimpa; Chakraborty, Santam; Goyal, Love; Saha, Saheli; Roy, Paromita; Zameer, Lateef; Mishra, Deepak; Parihar, Mayur; Das, Anirban; Chandra, Aditi; Biswas, Bivas; Mallick, Indranil; et al.
Abstract : PURPOSE: There are limited reports of quality metrics in glioblastoma. We audited our adherence to quality indicators as proposed in the PRIME Quality Improvement study. METHODS: This is a retrospective audit of patients treated between 2017 and 2020. After postsurgical integrated diagnosis, patients received radiotherapy (RT) with concurrent and adjuvant temozolomide (TMZ). Multiparametric magnetic resonance imaging at predefined times guided management. Numbers with proportions for indices were calculated. Survival was estimated using the Kaplan-Meier method. RESULTS: One hundred six patients were consecutively treated. The median age was 55 years (interquartile range of 47-61 years) with a male preponderance (68%). Ninety-six (90.6%) patients underwent subtotal resection, and 10 (9.4%) biopsy alone. Isocitrate dehydrogenase was wild-type in 96 (91%), and O 6 -methylguanine-DNA methyltransferase was unmethylated in 70 (66.0%) patients. Telomerase reverse transcriptase promoter was mutated in 64 (60.4%), and TP53 was mutated in 22 (20.8%). Concurrent radiation and TMZ were planned for 104 (98.1%), and radiation alone for 2 (1.9%). The median time to concurrent RT-TMZ was 36 days (interquartile range 30-44 days). All patients planned for RT-TMZ completed treatment, but only 81 (76%) completed adjuvant TMZ. Sixty-three (59%) completed six cycles, 18 (17%) received less than six cycles, and 25 (24%) did not receive adjuvant TMZ. At a median follow-up of 24 months (range 21-31 months), the median (95% CI) progression-free survival and overall survival were 11 (95% CI, 9.4 to 13.0) and 20.0 (95% CI, 15 to 26) months, respectively. CONCLUSION: Our patients met quality indices in most domains; outcomes are comparable with global results. Metrics will be periodically evaluated to include new standards and assess continuous service appropriateness.